Cognitive interference processing in adult survivors of childhood acute lymphoblastic leukemia using functional magnetic resonance imaging. (4th March 2022) - Svärd, Daniel; Erfurth, Eva Marie; Hellerstedt, Robin; Mannfolk, Peter; Mårtensson, Johan; Sundgren, Pia; Follin, Cecilia
Abstract: Background: Childhood acute lymphoblastic leukemia (ALL) is associated with cognitive impairment in adulthood. Cognitive interference processing and its correlated functional magnetic resonance imaging (fMRI) activity in the brain have not yet been studied in this patient group. Material: Twenty-six adult childhood ALL survivors (median [interquartile range IQR] age, 40.0 [37.0–42.3] years) were investigated at median age (IQR), 35.0 (32.0–37.0) years after treatment with intrathecal and intravenous chemotherapy as well as cranial radiotherapy (24 Gy) and compared with 26 matched controls (median [IQR] age, 37.5 [33.0–41.5] years). Methods: Cognitive interference processing was investigated in terms of behavioral performance (response times [ms] and accuracy performance [%]) and fMRI activity in the cingulo-fronto-parietal (CFP) attention network as well as other parts of the brain using the multisource interference task (MSIT). Results: ALL survivors had longer response times and reduced accuracy performance during cognitive interference processing (median [IQR] interference effect, 371.9 [314.7–453.3] ms and 6.7 [4.2–14.7]%, respectively) comparedwith controls (303.7 [275.0–376.7] ms and 2.3 [1.6–4.3]%, respectively), but did not exhibit altered fMRI activity in the CFP attention network or elsewhere in the brain. Conclusion: Adult childhood ALL survivors demonstrated impaired behavioral performance but no altered fMRI activity when performing cognitive interference processing when compared with controls. The results can be used to better characterize this patient group and to optimize follow-up care and support for these individuals.